Fundamentals of Entrepreneurship (ENT300) Business Plan : Custom Station / Ammar Firdaus Md Amran - Md Amran, Ammar Firdaus (2020)
Custom Station is a new business that allows people to custom design a t-shirt (specifically the design on the front or back) any way that they would like. By intelligently leveraging cutting edge technology, Custom Station will harness the power of computer sublimation to allow custom t-shirt printing in production runs as small as one unit. Custom Station will offer customers a variety of options for creating their own custom shirts. The majority of orders will be for t-shirts, however other style shirts will be available. My business will use Canon printer sublimation technology that allows a computer image to be applied to a t-shirt in a high quality, high resolution, economically feasible manner. This technology creates an image durable enough to withstand thousands of washing. Its photo-like quality, due to significantly higher printer resolution than anything on the market, will show off any image. The technology is cost effective enough to offer customers the ability to order just one unit. Most other competitors' costs prohibit printing custom shirts in one-off production runs. Finally, the customer may choose from an extensive library of existing images, supply their own image, or have an artist create an image for them. Competitive advantage is I setup this business in a very strategic place, it is because there is no other printing or custom services like I did in my place. Because of this is rural area, the nearest printing or custom shop will take everybody about an hour to get the service done.